Atribuições e competências gerenciais do coordenador pedagógico na educação profissional técnica de nível médio - Pereira, Fátima Aparecida (2014)
Assuming that two or more people who perform tasks in a coordinated manner constitute an organization, it s possible to say that the school is also an organization. And on this organization, the educational coordinator is the manager and the main actor in the context of school management. And for their assignments are performed on the best way, effectively, must have managerial skills to its development. In the literature that deals with management skills, among others, the managerial competence can be understood as a capacity to mobilize and apply knowledge (knowledge and know-how) and capabilities in a particular condition, in which place is settle resources and restrictions on specific situation, as defined by Ruas (2001). This study describes the job description of the position of pedagogical coordinator, and their managerial skills, in the grade of vocational technical education of high school. Thus, this approach served as the basis for evaluating their managerial competences of the pedagogical coordinator in the technical high school education in a school staff. Therefore, it was performed a empirical with qualitative method through a case of study. The study was conducted in a mid-level professional school of São Paulo, the capital, which has today close of 4,000 students enrolled. In the first stage, through documentary analysis, it was reviewed the educational legislation of this state and the regulations school. Following, adopting the technique of focus group data, it was collected information about the responsibilities of the pedagogical coordinator, in the research site. After it was done depth interviews were conducted with the coordinators of the school to validate the competences and responsibilities identified in the previous phase . The results show, first, that the legal responsibilities support the reflections on the functions and performance of the coordinator as school manager. The results also show that there was convergence on the understanding of roles and responsibilities about the legislation and regulation of the subject. Further the results indicate that the coordinators considered valid assignments and skills highlighted on this study. Also the pedagogical coordinators self - assessment proved valid in relation to the skills complexity required for the coordinators performance of professional technical high school education . The conclusion is that the study contributed to broaden the understanding of the subject in general, and the research context. The process of this research provided an opportunity of expansion of the interaction between teachers and pedagogical coordinators, as well as the study and discussion of managerial competencies.